Effects of vegetable oil source and dietary vegetable-fish oil ratio on the histological alterations of liver and intestine of juvenile Malaysian mahseer, Tor tambroides - Fard, Ehsan Ramezani; Kamarudin, Mohd Salleh (Academic Journals, 2013)
For many years, fish oil has been used as the major source of lipid in aquafeed production. However, the replacement of this marine origin ingredient with a sustainable resource such as vegetable oils is critically important. On the other hand, most of the vegetable oils are high in omega-6 polyunsaturated fatty acids while a diet rich in these fatty acids can increase liver lipid deposition in some fish. This study was conducted to investigate the effects of partial or total replacement of fish oil with different vegetable oil sources (sunflower and palm) on the histological alterations in the liver and intestine of juvenile Malaysian mahseer, T. tambroides. Five isonitrogenous and isocaloric diets were formulated in order to either completely or partially (50%) substitute fish oil with sunflower oil or palm oil. A diet without substitution was also used as a control. The effects of these diets on the histological alterations of liver and intestine of fish after a nine week feeding period were investigated. The results showed few inflammatory cells and lipid vacuoles in the liver of fish fed all the vegetable oil diets indicating minor hepatic steatosis. Lipid vacuoles were also observed in the intestinal wall of fish fed all the vegetable oil diets.